Decomposing and analysing the determinants of current accounts’ cyclicality: evidence from the Euro Area - Afonso, António (2022)
In this paper, we decompose the current account (CA) balance in 19 Euro area countries into cyclical and non-cyclical components. For the period 1999:Q1 to 2015:Q4, we compute income elasticities of imports and of exports via an alternative novel and improved approach by running time-varying coefficient models country-by-country. Then, in a panel set-up (and controlling for country-invariant characteristics), we uncover that terms of trade have a positive effect on both the cyclical and non-cyclical components of the CA, while the Global Financial Crisis, compensation of employees and the employment level have a negative effect on the cyclical component. Moreover, the crisis had a greater impact on the cyclical component of the CA due to movements in the real effective exchange rate. In addition, we find a negative effect of the crisis on the cyclical component of the CA for countries that received financial assistance from the European Union, notably Ireland, Portugal, Spain and Latvia.